2003
DOI: 10.1007/s00404-003-0506-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insulin on luteinizing hormone and prolactin secretion and calcium signaling in female rat pituitary cells

Abstract: Our findings suggest that insulin might contribute to LH hypersecretion. Insulin might be partially responsible for hyperprolactinemia. Since insulin did not affect Ca signaling, other components of the GnRH signal transduction pathway might be involved in LH hypersecretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…It is postulated that insulin could be another important modulator of gonadotroph secretory functions (1,22,42,51,52). In this study we observed the influence of insulin on the porcine pituitary secretory functions during the estrous cycle.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…It is postulated that insulin could be another important modulator of gonadotroph secretory functions (1,22,42,51,52). In this study we observed the influence of insulin on the porcine pituitary secretory functions during the estrous cycle.…”
Section: Discussionsupporting
confidence: 54%
“…Even minor metabolic dysregulation may lead to reproductive abnormalities, for example, hyperinsulinemia is frequently associated with an inadequate luteinizing hormone (LH) secretion. Although insulin, as a key metabolic hormone, is often recognized as an important factor influencing reproductive functions, the effects of insulin on the pituitary gland are still relatively little known (1,22,51,52). The regulating role of adipokines (i.e., leptin, ghrelin, and adiponectin) on the hypothalamic-pituitary-gonadal axis (HPG) is also documented (4,10,18,31,36,40).…”
mentioning
confidence: 99%
“…The hyperinsulinemia can potentiate gonadotropin-stimulated steroidogenesis in granulosa and thecal cells, by increasing the low-density lipoprotein (LDL) receptor, 3b-hydroxysteroid dehydrogenase, 17a-hydroxylase, and 17,20 lyase expression (Nestler & Strauss 1991, McGee et al 1995, Franks et al 1999, Poretsky et al 1999, Zhang et al 2000. In addition, insulin may act on the pituitary to increase LH release (Adashi et al 1981, Weiss et al 2003, Dorn et al 2004, Moret et al 2009). In agreement with these data, we observed both hyperinsulinemia and enhancement of progesterone serum levels in obese female rats.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia slows SHBG synthesis in the liver and thereby lowers circulating SHBG levels [24]. On the other hand, insulin has been shown to increase Luteinzing Hormone (LH) secretion in gonadotroph cells [25] and increases ovarian androgen production [26]. Elevated LH with a LH/Follicle-Stimulating Hormone (FSH) ratio of >2 is another common laboratory sign of PCOS.…”
Section: Shbg and Hyperandrogenism In Womenmentioning
confidence: 98%